Carbon nanofiber@ZIF-8 derived carbon nanosheet composites with a core–shell structure boosting capacitive deionization performance. Issue 34 (23rd August 2021) - Gong, Xinyi; Luo, Wanxia; Guo, Nannan; Zhang, Su; Wang, Luxiang; Jia, Dianzeng; Ai, Lili; Feng, Shizhan
Abstract : This work demonstrated the development of a hierarchical porous carbon–carbon composite used as an electrode material for capacitive deionization. Abstract : This work demonstrated the development of a hierarchical porous carbon–carbon composite used as an electrode material for capacitive deionization. The novel core–shell composite consisting of carbon nanofibers and N-rich porous carbon nanosheets (CNFZIF ) was obtained by in situ growth of zeolitic imidazolate framework-8 (ZIF-8) nanosheets on electrospun nanofibers. By tailoring the composition and porosity of CNFZIF, ion transport and adsorption in the composite were tuned to achieve a large desalination capacity and a high desalination rate. Thanks to the synergistic effect of its N-rich carbon surface, high hydrophilicity, large specific surface area and unique hierarchical porous structure, the engineered CNFZIF sample exhibited an excellent capacitive deionization performance with a maximum desalination capacity of up to 50.88 mg g −1 for NaCl solution and a high capacity retention rate of 97% after 30 cycles. Remarkably, CNFZIF also demonstrated high desalination capacities of 27.19 mg g −1, 25.35 mg g −1 and 20.46 mg g −1 for CaCl2, MgCl2, and KCl solutions, respectively. This work provided a new route for the design of advanced electrode materials, and therefore represents a major step forward in the development of electrodes for capacitive deionization applications.